EPIDEMIOLOGICAL AND OPERATIONAL ASSESSMENT OF TSETSE FLY AND TRYPANOSOMIASIS CONTROL INTERVENTIONS IN NIGERIA BETWEEN 2010 AND 2025: A SYSTEMATIC REVIEW AND META-ANALYSIS - Abubakar, Attahir; Abdullahi, Ramatu A.; Anchau, Rakiya G.; Imam, Ibrahim U.; Tamba, Zainab; Haruna, Muhammad K.; Sumayin, Hamra M.; Muhammad, Hafsatu (FUDMA Journal of Sciences, 2025)
African trypanosomiasis continues to pose significant public health and agricultural challenges in Nigeria, with evolving epidemiological patterns and emerging control challenges in the post-2010 era. Between 2010 and 2025, Nigeria implemented a range of interventions targeting tsetse (Glossina spp.) and trypanosomiasis, yielding heterogeneous outcomes across ecological zones. This PRISMA-compliant systematic review synthesizes findings from 95 peer-reviewed and grey literature sources to assess epidemiological trends, vector suppression efficacy, and operational constraints. Entomological indices and parasitological prevalence were extracted and analyzed using multivariate regression and pooled meta-analytic techniques. Pyrethroid-impregnated blue-black traps deployed in Yankari Game Reserve and Old Oyo National Park achieved significant reductions in Glossina tachinoides (−39.2%, 95% CI: 32.1–46.3) and G. morsitans submorsitans (−31.4%, 95% CI: 25.6–39.2). However, therapeutic failure of isometamidium chloride reached 42.6% in sentinel herds in Niger State (95% CI: 38.1–47.2; p < 0.001), indicating emergent drug resistance. While Human African Trypanosomiasis (HAT) incidence declined to fewer than ten confirmed cases nationally between 2017 and 2024, Animal African Trypanosomiasis (AAT) remains endemic in over 60% of livestock-rearing zones. Operational barriers—including fragmented surveillance, limited funding, and ecological shifts—continue to undermine AAT control. To advance toward elimination, we recommend: (1) national implementation of resistance allele surveillance via next-generation sequencing, (2) climate-informed, spatially optimized vector control, and (3) integration of whole genome sequencing into policy frameworks. Strategic investment in CRISPR-based genetic tools and One Health coordination will be essential to achieving trypanosomiasis elimination in Nigeria by 2030.
Keywords: Tsetse fly; Trypanosomiasis; Control interventions; Epidemiological assessment; Operational evaluation; Systematic review